Opportunities to enhance relational wellbeing through the National Disability Insurance Scheme: Implications from research on relationships and a content analysis of NDIS documentation. Issue 2 (14th March 2019) - Meltzer, Ariella; Davy, Laura
Abstract: Interpersonal relationships are critically important to ensuring that people with disability can access the benefits of individual funding models such as the National Disability Insurance Scheme (NDIS). The NDIS aims to enhance participants' self‐determination of supports and social and economic participation, but the emerging evidence indicates that achieving these policy outcomes requires stronger recognition of participants' relational context, even in a system focused on individual choice and control. This paper reports on a content analysis of the NDIS Act, NDIS Rules, Operational Guidelines, and Price Guide to examine the extent to which the scheme's conceptual foundations and funded supports in individual plans enable it to support relationships. Implications are drawn from this analysis and theory and evidence about the importance of relationships for disability policy and practice. The paper outlines three areas where the approach of the NDIS to relationships is limited and can be improved: first, by conceptualizing relationships as relationships rather than simply sources of informal support; second, through provisions to actively support relationships; and third, by considering the relational appropriateness of support provided by family, carers, and friends. It concludes with suggestions for how relational considerations can be enhanced, including implications for government in administering the scheme. Abstract : This paper examines the extent to which Australia's National Disability Insurance Scheme (NDIS) has been shaped in accordance with the "relational turn" in thinking about services for people with disability. Drawing on a content analysis of key NDIS documents, we argue that the success and sustainability of the scheme relies on participants' relational context. Fostering positive and fulfilling relationships should be a stronger focus of the scheme to ensure successful implementation and positive outcomes for participants.